Impact of Vitamin D Levels on HbA1C in Diabetic Obese Patients Hyderabad Sindh Based Study (Medical Forum Monthly, 2021)
Objective: To assess the impact of Vitamin D deficiency in patients having raised hemoglobin A1C (HbA1c) with obesity.Study Design: Descriptive / Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Liquate University Hospital, Hyderabad for six months from July 2016 to Jan 2017.Materials and Methods: This study included 143 patients. All the patients who fulfilled the inclusion criteria were evaluated for the deficiency of vitamin D level by taking 2cc venous blood sample in a disposable syringe and send to laboratory for analysis. A written proforma was filled by all the patients for participation in the study. The deficiency of vitamin D was labeled when <20ng//ml.Results: In our study, out of 143 cases with raised HbA1c and obesity 13.29 %(n=19) were between 30-45 years of age, while 86.71%(n=124) were between 46-60 years of age ± 53.58+5.37 years, Males were 46.85 %(n=67) and 53.15%(n=76) were females, mean Vitamin D level was 29.30+7.33. Frequency of vitamin D deficiency in diabetic patients having raised hemoglobin A1C(HbA1C) with obesity shown 21.68%(n=31) and p value was insignificant p>0.68.Conclusion: It has concluded that the impact of Vitamin D deficiency in patients having raised hemoglobin A1c (HbA1c) with obesity is higher and needs attention to address this issue in our population.